ANALISIS LIKUIDITAS DAN PROFITABILITAS PADA BANK UMUM KONVENSIONAL MILIK NEGARA TAHUN 2017-2021 - Dissa Rahita Pramutia (2022)
This writing aims to see the level of health of liquidity proxied by Loan to Deposit Ratio (LDR) and to see the level of health of profitability proxied by Return On Assets (ROA). The object in this paper is a State-Owned Conventional Commercial Bank or State-Owned Bank that has been registered with Bank Indonesia (BI)/Financial Services Authority (OJK). The data analysis method is by looking at the financial statements of each bank for the 2017-2021 period. The results of this data analysis indicate that in general the conditions of liquidity (LDR) and profitability (ROA) of state-owned banks have changed every year. In terms of liquidity (LDR) the average state-owned bank is in the fairly healthy criteria, while in terms of profitability (ROA) the average state-owned bank is in the very healthy criteria.